Psychology Education and Work Readiness Integration: A Call for Research in Australia - Schweinsberg, Ashleigh; Mundy, Matthew E.; Dyer, Kyle R.; Garivaldis, Filia (Frontiers in Psychology, 2021)
Supporting students to develop transferable skills and gain employment is a vital function of Universities in the era of the Fourth Industrial Revolution. A key area is work readiness which has steadily grown in importance over the last two decades as tertiary institutions increasingly aim to produce graduates who perceive and are perceived as work ready. However, a large majority of graduates report a lack of skills and confidence needed for the effective transition from study to work. This may be particularly problematic for disciplines that impart both discipline-specific and transferrable skills, such as psychology. The aim of this paper is to addresses the concept of work readiness within Australian psychological training and explore the need to shed light on and integrate work readiness within the pedagogy of psychology within Australia. Specifically, this paper calls for a review of work readiness skills developed in psychological courses to ensure industry needs are met. Beyond such a review, it is suggested that tertiary centers need to facilitate students in capturing and reflecting upon the transferable skills that they develop; and build assessments that allow students to demonstrate transferable skills in a meaningful way. Further, this paper proposes that work readiness skills be routinely mapped onto graduate attributes and course learning outcomes to be readily available by students so as to increase students’ potential to articulate their learnt work readiness skills once in the workplace.